Radiation Protection and Moral Theory. (1st August 1995) - Sumner, David; Gilmour, Peter
It seems likely that there is no threshold for the induction of cancer by ionising radiation. Hence even small radiation doses may result in a finite number of premature deaths if a large number of people are exposed. Various arguments are used to demonstrate that such deaths, if they occur, are acceptable; these arguments are shown to be flawed. Many of the arguments, and the ICRP's principle of justification, appear rooted in a utilitarian system of moral philosophy. Such a system is superficially attractive as it appears objective and rational; however, the objectivity may be an illusion masking the underlying aims of the interested parties.